2012
DOI: 10.1177/000348941212100412
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Tracheal Epithelium Using a Collagen Vitrigel—Sponge Scaffold Containing Basic Fibroblast Growth Factor

Abstract: Our technique for tracheal reconstruction using collagen vitrigel-sponge scaffolds with b-FGF application affords a feasible approach for accelerating the regeneration of the intraluminal surface and subepithelial layer of tracheal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…Neovascularization in replacement tracheas has been explored in only a few studies whose constructs contained vascular progenitor or endothelial cells obtained from adipose,24 bone marrow,25 or skin26 tissue. In vitro approaches to support vascularization of replacement tracheas have mostly relied on scaffold materials with potential angiogenic properties (e.g., decellularized allogeneic trachea27) or delivery of growth factors to drive angiogenesis 28. However, relying solely on host blood vessel infiltration may be insufficient in an orthotopic tracheal replacement because transplanted cells in the interior of the construct may die before becoming adequately microvascularized.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization in replacement tracheas has been explored in only a few studies whose constructs contained vascular progenitor or endothelial cells obtained from adipose,24 bone marrow,25 or skin26 tissue. In vitro approaches to support vascularization of replacement tracheas have mostly relied on scaffold materials with potential angiogenic properties (e.g., decellularized allogeneic trachea27) or delivery of growth factors to drive angiogenesis 28. However, relying solely on host blood vessel infiltration may be insufficient in an orthotopic tracheal replacement because transplanted cells in the interior of the construct may die before becoming adequately microvascularized.…”
Section: Discussionmentioning
confidence: 99%
“…To promote regeneration of the tracheal epithelium without a cell source, gel scaffold or growth factor was impregnated into gelatin hydrogel for tracheal defect repair [14,28,29]. Recently, collagen has been used for osteochondral regeneration [30][31][32], and in the present study, PC-NF with or without hUCS showed good cartilage regeneration.…”
Section: Discussionmentioning
confidence: 55%
“…To date only one growth factor, basic fibroblast growth factor (bFGF) has been used with collagen vitrigel sponge scaffold for tracheal regeneration [14]. Both autologous serum and umbilical cord serum owe their efficacy to the presence of various growth factors, like epidermal growth factor (EGF), acidic and basic fibroblast growth factor (FGF), platelet-derived growth factor, hepatocyte growth factor, vitamin A, transforming growth factor (TGF)-b, substance P, insulin-like growth factor (IGF)-1, nerve growth factor (NGF), fibronectin, and serum antiproteases, such as a2-macroglobulin [15].…”
mentioning
confidence: 99%
“…Further, the potential benefits, in terms of improved epithelialization, of the introduction of growth factors such as basic fibroblast growth factor (b-FGF) into the vitrigel will be examined [19].…”
Section: Discussionmentioning
confidence: 99%